Near-Field Single-Frequency Millimeter-Wave 3-D Imaging via Multifocus Image Fusion - Jing, Handan; Li, Shiyong; Cui, Xiaoxi; Zhao, Guoqiang; Sun, Houjun (IEEE antennas and wireless propagation letters, 2021)
The wideband radar system is usually exploited to obtain the 3-D image of the target under test. However, the wide bandwidth increases the system complexity and cost. Emerging techniques, such as the reconfigurable reflectarrays, reconstruct a near 3-D image via using single-frequency millimeter-wave (MMW) and near-field focusing of the beam, which greatly simplifies the system design, whereas the near-field focusing can only achieve a poor range resolution and a limited depth of focus. In this letter, we propose a multifocus image fusion method based on the criterion of minimum entropy, which can further be utilized for any kind of the MMW imaging system working at a single frequency. Simulations and experiments are presented to verify the effectiveness of the proposed method.